Target Therapy With Vaccinia Virus Harboring IL-24 For Human Breast Cancer - Deng, Lili (J Cancer, 2020)
Background: Breast cancer is a heterogeneous disease with high aggression and novel targeted therapeutic strategies are required. Oncolytic vaccinia virus is an attractive candidate for cancer treatment due to its tumor cell-specific replication causing lysis of tumor cells as well as a delivery vector to overexpress therapeutic transgenes. Interleukin-24 (IL-24) is a novel tumor suppressor cytokine that selectively induces apoptosis in a wide variety of tumor types, including breast cancer. In this study, we used vaccinia virus as a delivery vector to express IL-24 gene and antitumor effects were evaluated both in vitro and in vivo. Methods: The vaccinia virus strain Guang9 armed with IL-24 gene (VG9-IL-24) was constructed via disruption of the viral thymidine kinase (TK) gene region. The cytotoxicity of VG9-IL-24 in various breast cancer cell lines was assessed by MTT and cell cycle progression and apoptosis were examined by flow cytometry. In vivo antitumor effects were further observed in MDA-MB-231 xenograft mouse model. Results: In vitro, VG9-IL-24 efficiently infected and selectively killed breast cancer cells with no strong cytotoxicity to normal cells. VG9-IL-24 induced increased number of apoptotic cells and blocked breast cancer cells in the G2/M phase of the cell cycle. Western blotting results indicated that VG9-IL-24-mediated apoptosis was related to PI3K/β-catenin signaling pathway. In vivo, VG9-IL-24 delayed tumor growth and improved survival. Conclusions: Our findings provided documentation that VG9-IL-24 was targeted in vitro and exhibited enhanced antitumor effects, and it may be an innovative therapy for breast cancer.